2020
DOI: 10.3390/jpm10040230
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Prognostication in Transplant Candidates with Acute-on-Chronic Liver Failure

Abstract: We aimed to extensively investigate clinical markers that are sufficiently dynamic for prognosis of acute-on-chronic liver failure (ACLF). Defined by the Asian Pacific Association for the Study of the Liver (APASL) criteria, patients with ACLF on the liver transplant waitlist in a tertiary center were retrospectively reviewed. Laboratory results and severity scores at three time points (days 1, 7, and 14 after admission) were analyzed. From 2015 to 2019, 64 patients with ACLF were enrolled, of which 24 receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…PT-INR, an indicator of failed liver function, is also a marker for subsequent coagulation failure. Lu et al [ 26 ] recently demonstrated that a gradually increasing PT-INR index was associated with poor survival and indicated the need for fast-track liver transplant. Consistent with that result, the present study found that coagulation failure was also closely correlated with VDBP level when patients were stratified by clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…PT-INR, an indicator of failed liver function, is also a marker for subsequent coagulation failure. Lu et al [ 26 ] recently demonstrated that a gradually increasing PT-INR index was associated with poor survival and indicated the need for fast-track liver transplant. Consistent with that result, the present study found that coagulation failure was also closely correlated with VDBP level when patients were stratified by clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The heterogeneity in etiology leads to variable disease courses and has hampered accurate diagnosis and prognosis. Lu et al investigate dynamic changes in clinical markers, especially within the first 2 weeks of clinical admission, that aid in predicting poor prognosis and indicate the necessitation of fast-tracking therapeutic interventions or transplant prioritization [ 9 ].…”
mentioning
confidence: 99%